Transition economy institutions and international investments : case Kazakhstan - Summanen, Elena (2018)
Over last two decades, drastic changes in institutional environment of transition economies and its impact on attracting inward foreign direct investments (FDI) received close attention from the academic scholars in the field of international business. However, mechanisms of locating investments by Finnish firms to transition economies of Central Asia remain unexplored and require thorough investigation. In order to overcome the research gap, this qualitative case-study was conducted. The study aims at gaining a deeper understanding of institutional transition in the context of Kazakhstan economy and its influence on Finnish outward FDI. The institutional environment of Kazakhstan was constructed through the cognitive frames of various actors representing host and home countries. The theoretical paradigm of an institutional distance was incorporated in the scope of research to explore entry mode strategies of Finnish firms under distinctive institutional settings of both states. The cognitive frames of host and home country actors were elaborated through in-depth interviews and the method of content analysis. The actors represent facilitators of economic cooperation and Finnish firms doing business in Kazakhstan. The overview of Kazakhstan economy, institutional development and characteristics of trade between both states, presented in the case description, enriched the context of the study and enabled utilization of data triangulation. The evidences derived from the research provide solid grounds for several implications. The institutional transition is characterized by implementation of massive legislative, financial reforms and state programs with the purpose of creating transparent, accountable environment for foreign investors. Despite of the notable changes in regulative and normative domains, the presence of informal institutions such as corruption, political clans Zhuz diminish the quality of the institutional environment in terms of attractive location for investments. Discovered attributes of institutional distance insignificantly influence choice of entry mode to Kazakhstan. Finnish investments refer to transfer of technology and managerial competences to local parent firm as a source for development of non-commodity sectors. Close interaction between home and host countries’ institutions at governmental level, valid bilateral investment treaties effectively facilitate the Finnish FDI flow to Kazakhstan.